First record of Chelonibia testudinaria (Linnaeus, 1758)) (Cirripedia: Chelonibiidae) in northern Chile - Nicolás Zambrano; Alberto Ahumada; Juan Antonio Aliaga; Juan Francisco Araya (Gayana, 2022)
The first record of the epibiont cirripedium of sea turtles, Chelonibia testudinaria (Linnaeus, 1758), is described for northern Chile (the second record for the species in the country), extending the distribution of this species by almost 10 latitudinal degrees (about 1020 km), and filling a gap in its geographic range in the southeastern Pacific.